Analysis of ERP System Implementation in Improving Supply Chain Management Performance in Food Companies in Indonesia - Lubis, Fatimah Malini; Mutia, Dara; Kumalaningrum, Dwi Rahayu (Westscience Press, 2024)
Supply chain management is the most effective approach to maintaining competitive advantage and productivity in a company. Supply chain management and ERP systems are powerful tools to improve organizational performance and maintain competitive advantage. ERP systems focus on improving workflow and effective data utilization. This study aims to encourage ERP implementation in PT Indofood Tbk, PT Garuda Food, and PT Nestle Indonesia with a focus on supply chain management activities, implementation of enterprise resource planning systems and the benefits of ERP in improving supply chain performance in a company. The research method used is a literature review by collecting information from various journals to determine the success of ERP implementation in food companies in Indonesia. The final results show that ERP implementation in PT Indofood Tbk, PT Garuda Food, and PT Nestle Indonesia has made it easier for all division employees to make operational performance more effective and efficient and provide a positive contribution to the effectiveness of the company's SCM.